An urge for paradigm shift in psychometrics and psychiatric disease diagnosis - Khalil, Rehana (International Journal of Advances in Medicine, 2017)
Background: With the advancement in all modalities of medicine, the psychometrics and diagnosis of psychiatric illnesses also advanced in twentieth century but not accurate enough to label them explicit. Despite of extensive research in the field of mental health, there is a paucity of data on critical analysis of measuring methods of mental capacities, processes and diagnostic modalities of mental illnesses. The aim of current study was to explore the perception of all concerned stakeholders about the effectiveness of assessment methods in psychology and psychiatry. Methods: Semi-structured interviews with individual participants were conducted in Karachi, Pakistan during October 2015 to January 2016 for this qualitative study. Total 28 participants participated in the study, 7 participants per domain (doctors, psychologists, psychiatrists, and medical students/residents) were selected by homogeneous quota sampling. Interviews were transcribed, and identification of emerging and repeated themes was done. NVivo and concordance software were used to conduct content and discourse analysis, with simple counting methods. Microsoft excel was used for charts and tables. Each respondent gave written informed consent to participate in the study. Results: More than one third (39%) of the sample contemplated the current methods of psychological and psychiatric assessment as deficient to a major extent in accuracy while one third (36%) of them said it is insufficient to some extent and one participant stated it is completely deficient which makes 4% of the sample. Near half (43%) of respondents identified weakness of DSM IV and psychometrics as arbitrary, one fifth (21%) as use of checklist for diagnosis, and one third (36%) as unavailability of confirmatory tests. Almost half of the respondents (46%) put forward the proposal of listening the mind talk or self-talk of the patient/person while one third (36%) of sample suggested for a device which can help in abridging the subjective bias in assessment and confirmation. One fifth (18%) proposed to see the thought process and content of patient/person in their minds on a screen. Conclusions: A significant number of stakeholders of psychology and psychiatric fields affirmed the limitations of the current criteria for diagnosis for mental conditions and illnesses stated either by DSM or ICD and psychometrics. The stated constraints included inconsistency, use of checklist for diagnosis, and lack of confirmatory tests. There is a demand of more objective methods addressing the scientific impediments in advancement in the fields of psychology and psychiatry.